Risk factors for subclinical atherosclerosis in a prospective cohort of patients with systemic lupus erythematosus. Issue 11 (28th October 2003) - Doria, A; Shoenfeld, Y; Wu, R; Gambari, P F; Puato, M; Ghirardello, A; Gilburd, B; Corbanese, S; Patnaik, M; Zampieri, S; Peter, J B; Favaretto, E; et al.
Abstract : Objective: To evaluate traditional and non-traditional risk factors for subclinical atherosclerosis in systemic lupus erythematosus (SLE). Methods: A prospective cohort of 78 patients with SLE without overt atherosclerotic disease was studied. SLE clinical and laboratory parameters, disease activity and damage, treatment and traditional risk factors for atherosclerosis were evaluated. At baseline (T1) and after five years' follow up (T2), the serum levels of anti-oxidised palmitoyl arachidonoyl phosphocholine (oxPAPC), anti-heat shock protein 65, and anti-β2 -glycoprotein I antibodies and C reactive protein were tested. At T2, intima-media thickness (IMT) was measured using duplex carotid sonography. Thickened intima, plaque, mean IMT (m-IMT), and maximum IMT (M-IMT) were assessed. Results: A thickened intima was seen in 22/78 (28%) patients and plaque in 13/78 (17%). M-IMT and m-IMT were (mean (SD)) 0.77 (0.34) mm and 0.55 (0.15) mm, respectively. Patients with carotid abnormalities were significantly older, had higher blood pressure and total serum cholesterol levels, and had taken a higher prednisone cumulative dosage than those without any lesions. The carotid abnormalities were associated with renal disease and ECLAM >2 at T1, and with azathioprine treatment. In multivariate analysis, age and cumulative prednisone dose were associated with carotid abnormalities; age, hypertension, and anti-oxPAPC at T2 were correlated with higher M-IMT and m-IMT. Conclusions: In patients with SLE some non-traditional risk factors for atherosclerosis were identified, the most important of which was the cumulative prednisone dose. The role of some traditional risk factors, such as age and hypertension, was also confirmed. The predictive value of the new immunological and inflammatory markers of atherosclerosis seems to be masked by some disease related features.